Money does it better! Economic incentives, nudging interventions and reusable shopping bags: Evidence from a natural field experiment - Armenak Antinyan; Luca Corazzini (Cardiff University, Cardiff Business School, 2021)
Little is known about the impact of policy interventions other than taxes and bans aimed at reducing the demand for single-use plastic bags. We report results from a natural field experiment conducted in a large supermarket chain to test interventions based on nudges (information provision), financial bonuses (which are assigned through a competitive scheme) and free provision of reusable bags. We manipulate the type of the intervention, i.e., either a financial bonus or a nudge, and the presence of a reusable bag, i.e., either provided for free or not provided. Relative to the baseline with no intervention, both the bonus and the nudge considerably reduce the demand for single-use plastic bags. Free reusable bags are effective when combined with the bonus, albeit not effective when combined with the nudge. Finally, the bonus is more powerful than the nudge, irrespective of the absence or presence of reusable bags.
Keywords: C93; D12; D91; H23; 330; pro-environmental behavior; nudge; financial bonus; reusable bag; single-use plastic bag; randomized controlled trial